2022
DOI: 10.1039/d1nh00620g
|View full text |Cite
|
Sign up to set email alerts
|

Neuromorphic behaviour in discontinuous metal films

Abstract: Physical systems that exhibit brain-like behaviour are currently under intense investigation as platforms for neuromorphic computing. We show that discontinuous metal films, comprising irregular flat islands on a substrate and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Similar approaches of implementation of RC here discussed in nanowire networks can be extended to other complex nanostructured systems such as nanoparticle networks [58,59], discontinuous metallic films [60], nanotubes [61], polymeric substrates [43] and electrochemical systems [62]. While experimental hardware realization and characterization of multiterminal nanonetwork reservoirs with a large number of electrodes and a fine control of temporal dynamics still represent a challenge, it is important to point out that the here reported grid-graph model allows to explore different RC implementations and architectures in silico with low computational sources for a rational design of neuromorphic hardware.…”
Section: Discussionmentioning
confidence: 96%
“…Similar approaches of implementation of RC here discussed in nanowire networks can be extended to other complex nanostructured systems such as nanoparticle networks [58,59], discontinuous metallic films [60], nanotubes [61], polymeric substrates [43] and electrochemical systems [62]. While experimental hardware realization and characterization of multiterminal nanonetwork reservoirs with a large number of electrodes and a fine control of temporal dynamics still represent a challenge, it is important to point out that the here reported grid-graph model allows to explore different RC implementations and architectures in silico with low computational sources for a rational design of neuromorphic hardware.…”
Section: Discussionmentioning
confidence: 96%
“…Various physical reservoirs have been reported to meet these requirements. 20,21,23 Moreover, the 4-bit sequential coding for handwritten digits classification and compression of spatial dimension for feature space extraction through volatile memristive devices were revealed. 24,25 Milano et al demonstrated a bottom-up approach in constructing low-cost computing paradigm through self-organized nanowire networks for mapping the spatio-temporal inputs.…”
Section: Introductionmentioning
confidence: 99%